A corporate-crime perspective on fisheries: liability rules and non-compliance. (18th September 2015) - Jensen, Frank; Nøstbakken, Linda
Abstract: The existing fisheries economics literature analyzes compliance problems by treating the fishing firm as one cohesive unit, but in many cases violations are committed by agents acting on behalf of a firm. To account for this, we analyze the principal–agent relationship within the fishing firm. In the case where the firm directly benefits from illegal fishing, the firm must induce its crew to violate regulations through the incentive scheme. Within this framework, we analyze how the allocation of liability between fishing firms and crew affects quota violations and the ability to design a socially efficient fisheries policy. We show that without wage frictions, it does not matter who is held liable. However, under the commonly used share systems of remuneration, crew liability generally yields a more efficient outcome than firm liability. Furthermore, asset restrictions may affect the outcome under various liability rules.